2021
DOI: 10.3390/microorganisms9061285
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cellulose-Rich Organic Soil Amendments on Growth Dynamics and Pathogenicity of Rhizoctonia solani

Abstract: Cellulose-rich amendments stimulate saprotrophic fungi in arable soils. This may increase competitive and antagonistic interactions with root-infecting pathogenic fungi, resulting in lower disease incidence. However, cellulose-rich amendments may also stimulate pathogenic fungi with saprotrophic abilities, thereby increasing plant disease severity. The current study explores these scenarios, with a focus on the pathogenic fungus Rhizoctonia solani. Saprotrophic growth of R. solani on cellulose-rich materials w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 83 publications
0
6
0
1
Order By: Relevance
“…Next to that ambiguity, the adjective nature-based is both part of an analytical-scientific and of a metaphorical-rhetorical discourse. The use of carbon-rich substrates to specifically stimulate a guild of cellulolytic fungi that then outcompete other fungal guilds and that result, under certain specified conditions, in pathogen suppression (Clocchiatti et al, 2020, 2021) is an example of a nature-based practice rooted in empirical science. By contrast, claims that restoring food webs in agricultural soils makes the use of synthetic fertilizers superfluous is a nature-based solution rooted in rhetoric (Box 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to that ambiguity, the adjective nature-based is both part of an analytical-scientific and of a metaphorical-rhetorical discourse. The use of carbon-rich substrates to specifically stimulate a guild of cellulolytic fungi that then outcompete other fungal guilds and that result, under certain specified conditions, in pathogen suppression (Clocchiatti et al, 2020, 2021) is an example of a nature-based practice rooted in empirical science. By contrast, claims that restoring food webs in agricultural soils makes the use of synthetic fertilizers superfluous is a nature-based solution rooted in rhetoric (Box 4).…”
Section: Discussionmentioning
confidence: 99%
“…with higher lignocellulose concentrations). Clocchiatti et al (2020; 2021) showed that the addition of cellulose-rich soil amendments like wood sawdust or paper pulp can stimulate saprotrophic fungi and associated disease suppression (Table 2). It should be noted that adding soil amendments with high C:N ratios (including so-called fungal compost) can induce strong N immobilization during the first stages of decomposition and thus present a trade-off with crop productivity or fertilizer use (Clocchiatti et al, 2020).…”
Section: Nature-mimicry In Soil Biologymentioning
confidence: 99%
“…Dit is in lijn met resultaten uit de lange termijn proef te Vredepeel waar het effect van chitine op plant-pathogene nematoden en de schimmel Verticillium dahliea is aangetoond (Korthals et al, 2014). Ook cellulose-rijke producten kunnen soms ziektewering stimuleren (Clocchiatti et al, 2021). In een uitgebreid literatuuroverzicht tonen Bonanomi et al (2010) aan dat ziektewering verschilt per pathogeen en type organische stof dat wordt toegediend, maar ook dat er daarbinnen nog veel variatie is.…”
Section: Doelstellingunclassified
“…Bokashi might decompose faster and have a more short-term effect. Clocchiatti et al (2021) also noted this time-scale effect showing that application of different materials can initially increase the disease incidence but after four weeks increase soil suppressiveness. Furthermore, repeated organic amendment application, which can be desired to achieve higher arable soil quality, can improve the soil microbiome over time (Bonanomi et al, 2020(Bonanomi et al, , 2018Pérez-Piqueres et al, 2006) and therefore the general disease suppression capacity of the soil (Bonanomi et al, 2018;Schlatter et al, 2017).…”
Section: Introductionmentioning
confidence: 81%
“…The relationship between the type of organic amendment and soil suppressiveness is likely a combined result of organic amendment quality and the local composition of the microbiome (Clocchiatti et al, 2021(Clocchiatti et al, , 2020Luo et al, 2018;Mayerhofer et al, 2021). For example, when making compost, the aerobic process leads to an end product with a more recalcitrant stabilized organic fraction compared to fresh material because of the release of labile carbon (C) during composting (Luo et al, 2022;Mondini et al, 2003;Neher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%